Studying the Crystal Structure, Topography, and Anti-bacterial of a Novel Titania (TiO2 NPs) Prepared by a Sol-gel Manner - Fayyadh et al. (مجلة بغداد للعلوم, 2019)
In this research, titanium dioxide nanoparticles (TiO2 NPs) were prepared through the sol-gel process at an acidic medium (pH3).TiO2 nanoparticles were prepared from titanium trichloride (TiCl3) as a precursor with Ammonium hydroxide (NH4OH) with 1:3 ratio at 50 °C. The resulting gel was dried at 70 °C to obtain the Nanocrystalline powder. The powder from the drying process was treated thermally at temperatures 500 °C and 700 °C. The crystalline structure, surface morphology, and particle size were studied by using X-ray diffraction (XRD), Atomic Force Microscopy (AFM), and Scanning Electron Microscope (SEM). The results showed (anatase) phase of titanium dioxide with the average grain size of 110 nm at 500 °C calcination temperature, and (anatase- rutile) mixed phase of titanium dioxide with the average particle size of 118.1 nm at 700 °C calcination temperature. The anti-bacterial activity of the synthesis specimens was recorded through the Kirby-Bauer disc method (disc devotion method). The results displayed a pretty excellent antibacterial activity of TiO2 NPs to bacteria strains: Gram positive staphylococcus aureus, gram negative pseudomonas aeruginosa, and "gram negative escherichia coli. The sensitivity of the tested bacteria to TiO2 NPs depends on the oxidation state of the TiO2 NPs, particle size, volume, and the density of the unit cell. The small- average particle size of titanium dioxide particles showed high antibacterial activity against bacteria, while the larger- average particle size of titanium dioxide particles showed less antibacterial activity. The novelty of this production is the manufacturing of a novel kind of TiO2 NPs and achievement its best antibacterial activity.